Aggregative stability of colloidal 3D and 2D silver nanoparticles, stabilised by 11-mercaptoundecanoic acid, in the presence of singly charged cations - Malakhovsky, Pavel O.; Rashkevich, Alexey V.; Minakov, Egor A.; Artemyev, Mikhail (Journal of the Belarusian State University. Chemistry, 2022)
We studied the aggregative stability of colloidal silver quasi-spherical nanoparticles and two-dimensional nanoplates, stabilised by 11-mercaptoundecanoic acid, in the presence of phosphate buffers containing different singly charged cations (Li+ , Na+ , K+ , Cs+) and tris-HCl at pH 8.0 and concentration 0.02 mol/L which mimics the carbodiimide conjugation conditions of nanoparticles with biomolecules. Aggregation of silver nanoplates occurs in the presence of Na-phosphate buffer whereas at the same conditions the quasi-spherical nanoparticles retain colloidal stability. The difference in colloidal stability between 3D and 2D silver nanoparticles is due to the increase of the apparent acid dissociation constant on the nanoplates’ basal faces and the subsequent increase in specific bridging interactions nanoparticle – cation – nanoparticle which can be eliminated by introducing of non-ionic spacer (11-mercapto-1-undecanol) in the ligand layer. Silver nanoplates with mixed ligand layer have increased colloidal stability across the pH.
Keywords: colloidal silver nanoparticles; silver nanoplates; colloidal stability; ligand layer